Mid-Century Modern Exhibition Halls of Brno Exhibition Centre and Their Renovation - Lenka Štěpánková (Anuari d’Arquitectura i Societat)
Pavilions Y, C, and Z of the Brno Exhibition Centre, dating from the post-war period, are considered important monuments of Mid-century modern architecture in Czechoslovakia. However, they exhibit a number of operational shortcomings due to the time of their construction and the very nature of exhibition architecture intended originally only for seasonal use. The question of their future renovation and adaptation to a more sustainable operation is discussed in the context of their previous construction development, taking into account the peculiarities of the legislative environment in the Czech Republic and the specifics of exhibition and trade fair operations.